Students Eating Lunch on Library Patio (1960)
Students break for lunch in the Dexter patio. At the time, Dexter was the library. In the background is the Administration Building (now Cotchett Education) and the Agricultural Education Building, which was demolished in 1973 and is the current site of the Architecture Building.